Carbon credits as EU like it: Property, immunity, tragiCO2medy? - LOW, Kelvin F. K. (Institutional Knowledge at Singapore Management University, 2015)
While there have been many legal studies of the European Union Emissions Trading Scheme (EU ETS), none seem to have considered the EU ETS from the perspective of private law, particularly the private law issues that stem from the ambiguous legal nature of the 'carbon credit'. Such ambiguity translates into regulatory uncertainty and business risks of the sort that occurred in Armstrong DLW GmbH v Winnington Networks Ltd [2013] Ch 156, an English case involving fraud and 'stolen' European Union Allowances (EUAs). From an environmental law and policy perspective, uncertainty does not bode well for the EU ETS's regulatory effectiveness and environmental integrity. From a property law perspective, the legal nature of the EUA begs for clarification in order to give holders of EUAs certainty of their rights and obligations, the absence of which led to the litigation in Armstrong v Winnington taking on an unduly convoluted complexion. The authors argue that one of the critical failures of the EU ETS lies in its failure to properly define the fundamental legal nature of the EUA. While this omission to define can be explained away by deference to the principle of subsidiarity, it can be argued that the omission stems also from a failure to appreciate the legal nature of intangible property as well as a misunderstanding of the way in which registers of rights operate. Handicapped by conceptual failings, the EU ETS exposes participants to unnecessary uncertainty that national courts will find difficult to resolve.